The effect of alfentanil on maternal haemodynamic changes due to tracheal intubation in elective caesarean sections under general anaesthesia - Hosseini Valami, Seyedeh Masoumeh (Indian J Anaesth, 2015)
BACKGROUND AND AIMS: Endotracheal intubation can produce severe maternal haemodynamic changes during caesarean sections under general anaesthesia. However, administration of narcotics before endotracheal intubation to prevent these changes may affect the Apgar score in neonates. This study was designed to evaluate the effect of intravenous alfentanil on haemodynamic changes due to endotracheal intubation in elective caesarean sections performed under general anaesthesia. METHODS: Fifty parturients were randomly divided into two equal groups. Patients in the first group received alfentanil 10 μg/kg and in the second group received placebo intravenously 1 min before induction of anaesthesia for elective caesarean section. Haemodynamic parameters and bispectral index system (BIS) in mothers, peripheral capillary oxygen saturation (SpO(2)) and Apgar score in the newborn were assessed. RESULTS: Changes in systolic blood pressure were significant at 1, 5 and 10 min after intubation between two groups. Changes in diastolic blood pressure were significantly less in alfentanil group, 1 min after induction of anaesthesia and 1 min after endotracheal intubation. Mean heart rate at 1 min after induction and at 1 and 5 min after intubation also reduced significantly in this group. CONCLUSION: Alfentanil use was associated with decreases or minimal increases in maternal systolic and diastolic blood pressures and heart rate after endotracheal intubation.